MENAKAR KAPASITAS KEBIJAKAN DI BALIK INOVASI PROGRAM SUMPAH BERUANG KABUPATEN BANYUMAS - Risti Pratami; Kiki Darma Kasih; Risky Astagini Putri (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
The Sumpah Beruang (Waste to Money) program is an initiative by Banyumas Regency to manage waste through community empowerment. It shows great potential, but there has been no specific study describing the role of policy capacity in supporting the program. This study aims to examine the role of policy capacity in supporting the sustainability of the program. The research employs a qualitative approach using a literature review method, analyzing various relevant and credible sources on waste management policies. The findings reveal substantial policy capacity through the Banyumas Regency Regulation No. 6 of 2012 on Waste Management, which supports integrated waste management involving community participation. Through community involvement, the program has successfully reduced the volume of waste disposed of at landfills by 30%, created economically valuable products, and generated employment opportunities. The conclusion emphasizes that strengthening policy capacity through effective regulations, cross-sectoral collaboration (local government, private sector, and community), and integrated strategies are crucial factors in creating a sustainable waste management system.